HUNGER AS A MINIMIZING FACTOR: THE PRINCIPLE OF INSIGNIFICANCE IN HUNGER-DRIVEN THEFT (REMUNOM, 2023)
Cases of subtraction of low-value goods and essential food for human subsistence have become increasingly frequent and are widely publicized both in Brazil and in other countries. The WHO on March 11, 2020 declared a Covid-19 pandemic, which resulted in a significant decline in the income earned by the population. This article seeks to analyze the feasibility of applying the principle of insignificance in situations of starving theft, considering the need to balance the legal foundations with the humanitarian and social circumstances involved, in order to promote a fairer and more proportionate approach in the application of criminal law. The research has the following problem, from the analysis of decisions of the Brazilian legal system, is it possible to conclude that in cases of starving theft that the principle of insignificance has been applied? As the main objective to understand the historical evolution of the criminal type theft in the Brazilian legal system, as well as to understand the origin, evolution and applicability of the principle of insignificance. As secondary objectives, the socioeconomic and cultural factors that contribute to the practice of thefts considered famine will be studied, as well as the study of the impact that the covid-19 pandemic caused in that criminal type. In its application, one must take into account not only the value of the infringed legal interest, but also other socially and constitutionally relevant factors, so that there is no abuse or injustice.